Quality Characteristics of Honey Pineapple (Ananas comosus (L.) Merr.) with Minimally Processed Based on the Effect of Packaging Type - Kavadya Syska (Program Studi Teknik Pertanian, Fakultas Pertanian, Universitas Jenderal Soedirman, 2022)
Fresh fruit that is minimally processed is susceptible to damage due to loss of natural protection, including honey pineapple. One storage technique that can minimize damage to minimally processed fruit is low temperature storage using plastic film packaging. The purpose of this study was to examine the effect of the type of packaging on changes in the quality of minimally processed fruit. Storage was carried out at 5˚C, 10˚C, and 27˚C. The types of packaging used are stretch film (SF) and low density polyethylene (LDPE) packaging. Quality changes observed included weight loss, moisture content, hardness, and total dissolved solids. The results showed that changes in the quality of honey pineapple during storage were influenced by temperature and type of packaging. LDPE packaging is not highly recommended for minimally processed honey pineapple packaging. Based on observations of weight loss, moisture content, hardness, and total dissolved solids, the best packaging for minimally processed honey pineapple storage is stretch film packaging stored at 10˚C.